Toward regenerative tourism: The role of regenerative technologies and storytelling in the perception of regenerative value and tourist satisfaction - Safa Chaieb (Journal of Rural Tourism, 2026)
Purpose - This study examines how technologies and storytelling shape the perception of regenerative value within tourism experiences, and how this perception impacts visitor satisfaction. It is grounded in the growing movement toward regenerative tourism, which emphasizes restoring and enriching destinations rather than merely sustaining them. Methodology/Design/Approach - A conceptual model was developed to capture both the direct and indirect (mediated) effects of technologies and storytelling on visitor satisfaction. Data collected from 162 respondents were analyzed using Structural Equation Modeling (SEM) and Bootstrapping with 5,000 resamples to test the hypothesized relationships.Findings - The results reveal that technologies and storytelling significantly influence visitor satisfaction. However, their effects are largely mediated by visitors’ perception of contributing positively to the destination. Among the variables, perceived regenerative value emerged as the strongest predictor of overall satisfaction.Originality/Value - This study extends existing theories of value co-creation, transformational tourism, and experience design. It highlights the strategic role of technology and narrative as key enablers of meaningful, regenerative travel experiences that go beyond traditional notions of sustainability.